The principles of political economy and taxation - Ricardo, David (Mineola Dover Publications, 2004)
This landmark treatise of 1817 formulated the guiding principles behind the market economy. Author Ricardo, with Adam Smith, founded the classical system of political economy, a school of thought that dominated economic policies throughout the 19th century and figured prominently in the theories of John Stuart Mill and Karl Marx.
Includes bibliographical references (p. xiv) and index.
Keywords: Economics